Arthritis of mice induced by Mycoplasma arthritidis. Humoral antibody and lymphocyte responses of CBA mice. - Cole, B C (1976)
Peak arthritis occurred 7 days after intravenous injection of CBA mice with Mycoplasma arthritidis and persisted in some animals for 84 days. A marked leucocytosis was apparent for the first 21 days. Complement-fixing antibodies reached a peak 14 days after injection of the organisms and persisted at high levels for 84 days. Metabolic-inhibiting and mycoplasmacidal antibodies were present but at much lower titres.